BUDAYA BACA GURU DAN SISWA SEKOLAH DASAR DI KOTA YOGYAKARTA - Pujiati Suyata (Universitas Negeri Yogyakarta, 2003)
Abstract School reading culture is one of the thinking quality improvement assets of the individual which has potential for raising the graduate quality. This investigation was an effort to get the idea of reading culture in school, teachers, and pupils, in the city of Yogyakarta. A study was done using 42 primary school teachers of seven schools in the city of Yogyakarta. In addition, 324 pupils taught by these teachers were also involved in this study. A questionnaire was developed and tested, used to collect the data. Description method analysis was used. The result indicated as following. (1) the reading culture of the primary school teachers in Yogyakarta city was found generally high supported by reading facilities at home as well as in school. It had an association with the fact that many teachers succeeded with their university program. (2) Primary school pupils’ reading culture was found high both those who had reading facilities at home and those who had not. The correlate of the reading culture was the education and the occupation their parents. Keywords: reading culture, teacher and pupil, primary school